Transthoracic Coronary Flow Data at Rest Predict High-Risk Stress Tests - Zagatina, Angela; Zhuravskaya, Nadezhda; Vareldzhyan, Yuliya; Kamenskikh, Maxim; Shmatov, Dmitry; Benacka, Jozef; Kucera, Martin; Kruzliak, Peter (Acta radiologica (Stockholm, Sweden, 2018)
Background Several recent studies have reported the opportunity to diagnose significant narrowing of the coronary arteries without stress testing using local flow acceleration. Purpose To define how often patients with increased coronary flow velocities at rest (≥ 0.70 m/s) have a positive exercise echocardiography test. Material and Methods A total of 150 patients scheduled for exercise echocardiography were studied using transthoracic Doppler echocardiography in order to assess coronary artery flow velocity before exercise. Pulsed wave Doppler registered blood flow velocity placed on the color signal. The maximal diastolic velocity of coronary flow was measured. Results Of participants, 16% had a velocity of more than 0.70 m/s in the left main/proximal left anterior/proximal left circumflex arteries (LM/pLAD). A significant correlation was observed between the value of the maximal velocity in LM/pLAD and the ejection fraction at the peak of exercise ( r ≈ -0.39, P < 0.0001); between the value of the maximal velocity in LM/pLAD and index of wall motion abnormalities (IWMA) at the peak of exercise ( r ≈ 0.44, P < 0.0001); and between the value of the maximal velocity in LM/pLAD and dIWMA ( r ≈ 0.41, P < 0.0001). Afterwards, severe ischemia in stress echocardiography tests was observed in this group. The average IWMA of these tests was found to be 2.3. Sixty-two angiograms were available for comparison with Doppler data. Conclusion There is a significant correlation between the value of the maximal velocity in LM/pLAD/pLCx at rest and the severity of wall motion abnormalities during exercise tests.
Keywords: Transthoracic echocardiography; exercise stress echo; hodnocení rizik; lidé středního věku; koronární cirkulace; odpočinek; Doppler flow aliasing; Echocardiography, Stress; lidé; Middle Aged; Echocardiography, Doppler; zátěžový test; Predictive Value of Tests; Female; Risk Assessment; Male; ženské pohlaví; Exercise Test; dopplerovská echokardiografie; Humans; mužské pohlaví; zátěžová echokardiografie; prediktivní hodnota testů; Coronary Circulation; Rest; coronary artery Doppler